Antibiotic resistance in Campylobacter and other diarrheal pathogens isolated from US military personnel deployed to Thailand in 2002–2004: a case–control study - Carl J. Mason; Siriporn Sornsakrin; Jessica C. Seidman; Apichai Srijan; Oralak Serichantalergs; Nucharee Thongsen; Michael W. Ellis; Viseth Ngauy; Brett E. Swierczewski; Ladaporn Bodhidatta (Tropical Diseases, Travel Medicine and Vaccines, 2017)
Abstract Background Campylobacter continues to be an important cause of diarrheal disease worldwide and a leading cause in Southeast Asia. Studies of US soldiers and marines deployed to Thailand for a 2 to 3 week field exercise provide a unique population in which to study traveler’s diarrhea. Methods A case–control study of 217 deployed military personnel was conducted from 2002 through 2004. Of these, 155 subjects who presented to a field medical unit with acute diarrhea were enrolled as cases. These subjects referred an additional 62 diarrhea-free colleagues who served as controls. Frequencies of isolation of Campylobacter spp. and other enteric pathogens were compared in cases and controls, and antibiotic resistance of isolates was described. Results Of the 155 subjects with diarrhea, Campylobacter spp. was the most commonly identified pathogen, found in 54 (35%) of the subjects, followed by non-typhoidal Salmonella species found in 36 (23%) subjects. Of the 57 separate C. jejuni and C. coli isolates from these individuals, 51 (89%) were resistant to ciprofloxacin by the disc diffusion method. Nearly one-third of the Campylobacter species were resistant to ampicillin and trimethoprim-sulfamethoxazole. Resistance to azithromycin remained low at 2% (n = 1). Conclusions The significant morbidity and marked fluoroquinolone resistance associated with Campylobacter infections in Thailand are important considerations for clinicians providing counseling on appropriate antibacterial regimens for civilian and military travelers.